Analisis Rasio Keuangan Untuk Menilai Kinerja Keuangan Pada PT. Astra Internasional, Tbk - Nuristiqamah isti; Alwi Alwi; Aliah Pratiwi (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the financial performance of PT Astra International Tbk using a financial ratio analysis approach. The financial ratios analyzed include liquidity, solvency, activity, and profitability ratios. This research is a descriptive study with a quantitative approach, utilizing annual financial statements of PT Astra International Tbk that are officially published through the Indonesia Stock Exchange. The results of the analysis indicate that the company’s liquidity ratios are in a fairly good category, reflecting its ability to meet short-term obligations. The solvency ratios show that the company’s dependence on debt remains under control, resulting in relatively low financial risk. The activity ratios indicate that the effectiveness of the company in utilizing assets to generate sales is still fluctuating. Meanwhile, the profitability ratios show fairly good performance, although there is a decline in certain periods. Overall, the financial performance of PT Astra International Tbk can be considered fairly stable and sound. However, the company needs to continuously improve the effectiveness of asset management and maintain profitability in order to remain competitive amid market dynamics.